Peter Rabbit [videorecording (DVD)] - Gluck, Will; Byrne, Rose; Neill, Sam; Ridley, Daisy, 1992-; Potter, Beatrix, 1866-1943 (Sony Pictures Home Entertainment, 2018)
Feature adaptation of Beatrix Potter's classic tale of a rebellious rabbit trying to sneak into a farmer's vegetable garden.